Peran Suami-Istri Prespektif Tafsir Maqhasidi - Hikmawati, Risma; Kholifah, Ayu (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
When a husband loses his job and is unable to fulfill his role as a breadwinner, there is a phenomenon where the husband loses direction in the household and is not aware of other roles such as participating in domestic work or being involved in caregiving. One of the possible reasons is that it originates from the popularity of texts interpreting the role of husband and wife, such as in the interpretation of the Al-Quran, Surah al-Baqarah verse 233. In discussions regarding the role of husband and wife, for some contemporary scholars it is considered more appropriate to use the maqhasidi interpretation method. This interpretation method tries to interpret the verse and weigh it against the principles of maqashid sharia, where there is the main principle, that the laws conveyed in the Koran must have a maslahah goal. This research attempts to analyze the role of husband and wife from the perspective of maqhasidi. Research method is qualitative with analytical descriptive. The results of the research show that the use of the Maqhasidi interpretation perspective has different interpretation results from the textualist interpretation, where from the maslahah perspective, the roles of husband and wife are placed equally and mutually.